Human sorting nexin 2 protein interacts with Influenza A virus PA protein and has a negative regulatory effect on the virus replication - TURAN, KADİR (SPRINGER, 2022)
Background Replication of the influenza A viruses occurs in the cells through the viral RdRP consisting of PB1, PB2, and PA. Several cellular proteins are involved in these processes. This study aims to reveal the interaction between human SNX2 protein and the PA protein and the effects of the SNX2 on the virus replication. Results To identify potential host interacting proteins to the PA, yeast two-hybrid assay was carried out with HEK293 cell cDNA library and the PA as a bait. We focused on SNX2 protein, which interacts with the PA in the yeast cells. By using the co-immunoprecipitation assays, it has been demonstrated that the amino-terminal part of the PA was important for binding to the SNX2. Immunolocalization of the proteins in HeLa cells supported this interaction. Knockdown of the SNX2 with siRNA in the cells resulted in a significant increase in both viral transcripts and virus growth. However, the increase of SNX2 in transfected cells didn't cause a significant change in the viral RdRP activity in minireplicon assay. This may suggest that the negative effect of SNX2 on the virus replication could be saturated with its authentic intra-cellular amount. Conclusions This study revealed that the SNX2 and PA protein interact with each other in both yeast and HEK293 cells, and the SNX2 has a negative regulatory function on the virus replication. However, more knowledge is required to elucidate the action mechanism of the SNX2 on the influenza A virus replication at the molecular level.
Keywords: Influenza a viruses; SNX2; Influenza RdRP; Influenza PA protein; POLYMERASE; RETROMER; ASSOCIATION; EXPRESSION; TRANSPORT; ELEMENTS; COMPLEX; REGION; GENES; NS1